Fatty Acid Composition and Technological Quality of the Lipids Produced by the Microalga Scenedesmus dimorphus 1237 as a Function of Culturing Conditions - A. Cicci; M. Bravi (Chemical Engineering Transactions, 2016)
Scendesmus dimorphus is an oleaginous eukaryotic microalga, able to produce and accumulate lipids up to a weight fraction of 49%. Aim of the present work is investigating the production of lipids by S. dimorphus 1237 and characterize them at a fatty-acid level. The variables accounted for were: the nutrient supply level and the extraction system (Soxhlet and bead beating). Two lipid phases were extracted by sequential, twin-solvent system (hexane and a chloroform:methanol mixture), the quantified gravimetrically and analyzed for their individual fatty acid composition by gas chromatography. The maximal total lipid concentration was measured by Soxhlet extraction in deficient nitrogen conditions (0.88 mg/L) and was found to be 49% (dw). In particular, palmitic acid was increased from 15% to 58% under phosphorous starvation and oleic acid content was increased from 8% to 40% under nitrogen starvation. Finally palmitic, palmitoleic and linolenic acid represented together more than 70% of the extracted lipids.